The Effects of antecedents and macro-social marketing strategies in retention of Women in Science, Technology, Engineering and Mathematics (STEM) careers in Kenya - Nguti, Lucy Esther Kuthea (Strathmore University, 2019)
The Science, Technology, Engineering and Mathematics (STEM) labour market is plagued with a wicked gender diversity issue attributed to women leaving the field at an alarmingly high rate. This is perturbing since a diverse. Labour market in STEM is vital to the growth of the economy and general development of nations, as it ensures proper utilization of human capital, enhances creativity and satisfaction within the diverse customer base. It is thus not surprising that this global phenomenon particularly afflicts developing nations, more so in Africa, as women make up only 30% of the STEM labour market. However, there is little evidence from developing nations on the phenomenon since most studies conducted were in 'industrialized countries'. Further compounding this travesty is the notable paucity of literature on the issue of retention within career paths, particularly within STEM. Therefore, this study posits that to retain women in STEM careers it is essential to use a macro social marketing perspective to gain a system wide understanding of the complicated problem in order to create successful multilevel retention strategies. This study therefore implemented a sequential exploratory mixed method design as it sought to establish the career retention intentions, the antecedents of retentions behavior of women in the STEM labour market in Kenya and how the antecedents influenced retention behaviors. The sequential exploratory mixed method design had an initial qualitative phase of data collection and analysis, followed by a phase of quantitative data collection using a survey tool designed from the qualitative results. The qualitative results comprised Eleven antecedents of retention intentions, which were, 'support of family and friends', 'work environment', 'passion', 'sense of belonging', 'work family conflict', 'career mentorship', 'self-efficacy', 'expectation fulfilment', 'perception of societal contribution', 'Career sustainability and growth' and 'female role models' . The quantitative data collected using the survey was analysed using descriptive statistics, Pearson's Correlation and multiple regressions to validate the qualitative findings. Women in STEM were found to have low retention intentions. A 75.6%ofthose with low retention intentions were respondents who had less than five years working experience. All the antecedents, except work-family conflict had a positive significant relationship with retention intentions. Work-family conflict had a negative relationship that was not statistically significant. Furthermore, 'sense of belonging', 'support of family and friends, 'career sustainability and growth', 'expectation fulfilment' and 'passion', and explain78.4% of the variance of retention intentions. It can thus be conciliated that the retention of women in STEM careers in Kenya, a developing country, is a concern, a finding that is consistent with similar studies conducted in developed countries. The antecedents and their relationships to each other were further mapped into a behavioral ecological framework and it was determined that relationships existed between several actors from all levels of the system environment and the factors of influence that were raised. This study enhances the discussion on career retention as it not only identifies factors that influence retention in STEM careers, but it also shows, using systems thinking, that the factors and actors in the STEM career system are interrelated. The interrelationships between the antecedents point to multiple root causes of the lack of retention among Women in STEM careers in Kenya. Multilevel, system wide interventions that will Influence all the relevant players in the system need to be created and implemented for effective change to take place in the STEM career system in Kenya. Furthermore, this study addressed a contextual gap as it contributes to the subject knowledge of career retention among women in STEM in Kenya, a developing country in Africa; previous studies on women in STEM were mainly conducted in developed countries. It also unveils the society level efficacy of macro-social marketing in career management and in a developing country context.
Submitted in total fulfillment of the requirements for the Degree of Doctor of Philosophy in Marketing at Strathmore University